Investigation on the self-starting Mamyshev oscillator with low threshold. (1st August 2022) - Guo, Wei; Lu, Sihua; He, Qiurun; Zhang, Baofu; Ma, Shanchao; Jiao, Zhongxing; Lai, Tianshu
Abstract: We have demonstrated a mode-locked Mamyshev oscillator based on a single-mode-fibre configuration with low threshold. The influences of spectral filters and the pump power on the output laser characteristics have been investigated. In the case with spectral-filter central wavelength far away from the peak of gain spectrum, the laser pulses have deviated slightly from similariton evolution with gain-shaping under high pump power. Moreover, self-starting mode-locking operation has been realized when the pump power was only 520 mW, which might benefit from the appropriate polarization conditions and small spectral filter separation. The laser can generate 1.89 nJ ultra-short pulses with 20 dB spectral width of 54.6 nm. The pulse duration can be compressed externally to 64.69 fs with the peak power of 21.3 kW.